Infección por helicobacter pylori y riesgo de lesión colorrectal de origen neoplásico - Meregildo Carranza, Carlos Jesús Junior (2017)
Infection by Helicobacter pylori (HP) is present in at least 50% of the world population, in developing countries like Peru the prevalence has remained similar over time. This infection is not only attributed to the negative effects on the gastric mucosa, but also to other effects, such as alterations in the epithelium of the colorectal mucosa, which would develop carcinogenic lesions in these tissues. Objective: To determine whether HP infection is a risk factor for neoplastic colorectal lesion in patients treated in the HRDT to date. Materials and methods: A retrospective analytical case and control study was carried out. 308 clinical histories were evaluated, of which 71 cases were extracted (patients with a diagnosis of colorectal lesion of neoplastic origin) and 71 controls (patients without diagnosis of colorectal lesion of neoplastic origin). In addition, the previous diagnosis of HP infection evidenced in gastric or duodenal biopsy in the same group of patients was verified. Chi square and Odds Ratio (OR) were calculated with a 95% CI and a level of significance of p <0.05. Results: In patients with a colorectal lesion of neoplastic origin, the frequency of HP (+) was 57.7 % and that of HP (-) was 42.3 %. When evaluating the association, an OR was found: 2.85 (95% CI: 1.43-5.65, p = 0.002). Conclusion: Previous HP infection is a risk factor for colorectal lesion of neoplastic origin